Penerapan Metode Tahsin Berbantuan Aplikasi Genially dalam Meningkatkan Kemampuan Membaca Al-Qur’an Pada Kegiatan Literasi Qur'an Kelas VIII di Sekolah Menengah Pertama: The Application of the Genially Application-Assisted Tahsin Method in Improving the Ability to Read the Qur'an in Qur'an Literacy Activities for Class VIII in Junior High Schools - Intan Maharani Baso; Andi Riawarda; Nur Fakhrunnisaa (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study discusses the application of the Tahsin method assisted by the Genially application to improve students' ability to read the Qur'an in Qur'an Literacy activities. This study aims to determine the improvement in the ability to read the Qur'an in the application of the Tahsin method assisted by the Genially application in class VIII B SMPN Tana Lili. This type of research uses classroom action research (CAR). The subjects of the study were 23 students of class VIII B at SMPN 2 Tana Lili. Data collection techniques were through tests, observation and documentation. Data analysis techniques used were quantitative and qualitative data analysis. The results of this study indicate that the test scores of students' ability to read the Qur'an increased by 39% from cycle I to cycle II, with a classical completeness score of 91% (complete). The score obtained from the N-Gain test was 0.65 or 65% with a fairly effective category. The results of this study indicate that the application of the Tahsin method with the help of the Genially application can improve the Qur'an reading skills of class VIII B students at SMPN 2 Tana Lili. Therefore, the Tahsin method can be recommended for use in the learning process.